Porous silicon carbon negative electrode material and preparation method and application thereof

By preparing porous silicon carbon anode material and using the carbon frame structure of nano-silicon and pinecone powder, the problem of rupture caused by volume expansion of silicon materials in lithium-ion batteries is solved, and the cycle stability and life of the battery are improved.

CN119797367AActive Publication Date: 2025-04-11XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510011113.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

Traditional carbon negative electrode materials have low energy storage capacity. The volume expansion and contraction of silicon materials during lithium ion embedding and deintercalation leads to the easy rupture of the electrode materials, reducing cycle stability and long-term durability.

Method used

Nanosilicon and pinecone powder are used as raw materials to prepare porous silicon carbon negative electrode materials through ultrasonic dispersion, freeze-drying, carbonization treatment, acid etching and airflow grinding and crushing, forming a carbon frame structure to limit the expansion of silicon.

Benefits of technology

It improves the stability and life of silicon negative electrode materials, extends battery life, enhances cycle stability, and reduces production costs, making it suitable for industrial scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797367A_ABST
    Figure CN119797367A_ABST
Patent Text Reader

Abstract

The invention discloses a porous silicon carbon negative electrode material and a preparation method and application thereof, the preparation method comprises the following steps: (1) mixing and stirring nano silicon and a binder emulsion, and then sequentially carrying out ultrasonic dispersion and freeze drying to obtain a nano colloidal silica material; (2) crushing pine cone powder and a nano colloidal silica material respectively, then mixing, and then performing high-temperature carbonization treatment on the mixture to obtain a silicon-carbon composite material; (3) stirring and mixing the silicon-carbon composite material with an acid solution, carrying out etching treatment, filtering the obtained etching solution, and washing until the pH value is 6-7 to obtain a washing material; and (4) drying the washing material, performing jet mill crushing, and screening to remove magnetism, thereby obtaining the porous silicon-carbon negative electrode material. The porous silicon-carbon negative electrode material is prepared by taking the nano silicon and the pine cones as the raw materials, the raw materials are wide in source and low in cost, and the prepared porous silicon-carbon negative electrode material has relatively high porosity and good cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode materials for lithium ion batteries, and in particular, the present invention relates to a porous silicon-carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] In modern lithium-ion batteries, although traditional carbon negative electrode materials have reliable performance, their energy storage capacity is relatively low. In contrast, silicon materials have higher theoretical specific capacity and lower lithium ion diffusion coefficient, making them an ideal high-capacity negative electrode material. However, due to the volume expansion and contraction of silicon during the insertion and extraction of lithium ions, silicon electrode materials are prone to rupture and capacity decay, greatly reducing the cycle stability and long-term durability of the electrode. Carbon materials have good stability. By introducing carbon into silicon materials, the stability and life of silicon negative electrode materials can be effectively improved. In addition, carbon materials can improve the conductivity of silicon and provide an elastic support structure to reduce the stress caused by volume expansion, further improving the cycle stability and electrode life of silicon negative electrode materials. However, most of the carbon materials added to silicon-carbon negative electrode materials are petroleum asphalt, and petroleum is a non-renewable resource, and resources are becoming increasingly scarce. For this reason, new carbon materials need to be selected for the preparation of silicon-carbon negative electrode materials. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the embodiment of the present invention provides a porous silicon-carbon negative electrode material and a preparation method and application thereof.

[0004] In a first aspect, an embodiment of the present invention provides a method for preparing a porous silicon-carbon negative electrode material, comprising the following steps:

[0005] (1) mixing nano-silicon and a binder emulsion, and then sequentially performing ultrasonic dispersion and freeze drying to obtain a nano-silica gel material;

[0006] (2) crushing the pine cone powder and the nano-silica gel material separately, mixing them, and then subjecting the mixture to high-temperature carbonization treatment to obtain a silicon-carbon composite material;

[0007] (3) stirring and mixing the silicon-carbon composite material with an acid solution, performing an etching treatment, filtering and washing the obtained etching solution to a pH value of 6 to 7, and obtaining a washed material;

[0008] (4) After the washed material is dried, it is subjected to air flow milling, sieving and demagnetization to obtain the porous silicon-carbon negative electrode material.

[0009] The embodiment of the present invention adopts nano-silicon and pine cones as raw materials to prepare silicon-carbon negative electrode materials. The vacancies between the nano-silicon and the pine cone-derived carbon can provide silicon with sufficient expansion space, and the stability of the electrode material can be maintained during the lithium insertion and removal process, thereby extending the battery life. The embodiment of the present invention also utilizes an acid solution to etch the silicon-carbon composite material, so that the structure of the silicon-carbon composite material is transformed into a porous structure, further reserving space for the volume expansion of silicon. At the same time, the carbon framework around the silicon limits the expansion of silicon, which can solve the failure problem of the silicon negative electrode material during the lithium insertion and removal process. The preparation method in the embodiment of the present invention is simple in process, easy to operate, highly efficient, has a wide source of raw materials, is low in cost, and is suitable for industrial-scale production.

[0010] In some embodiments, in step (1), the mass ratio of the nano-silicon to the binder emulsion is (7-10):1;

[0011] Preferably, the particle size of the nano-silicon is 20 to 60 nm;

[0012] Preferably, the binder emulsion includes at least one of styrene-butadiene rubber emulsion, silane coupling agent A-171, silane coupling agent KH-560, and silane coupling agent KH-570.

[0013] In some embodiments, in step (1), the mixing and stirring time is 30 to 90 minutes, the ultrasonic dispersion time is 30 to 60 minutes, and the freeze-drying time is 24 to 72 hours.

[0014] In some embodiments, in step (2), the mass ratio of the pine cone powder to the nano-colloid material is (10-12):1.

[0015] In some embodiments, in step (2), the high temperature carbonization process is as follows: purifying and removing impurities from the mixture at 200° C. for 30 to 60 minutes under an inert gas atmosphere, then heating the mixture to 1200 to 1600° C. at a heating rate of 5 to 10° C. / min, keeping the temperature for 1 to 3 hours, and cooling the mixture to room temperature;

[0016] Preferably, the inert gas includes at least one of nitrogen and argon, and the flow rate of the inert gas is 1 to 5 m / s.

[0017] In some embodiments, in step (3), the acid solution includes at least one of hydrochloric acid solution, citric acid solution, sulfuric acid solution, and nitric acid solution;

[0018] Preferably, the mass concentration of the acid solution is 5-20%.

[0019] In some embodiments, in step (3), the stirring and mixing speed is 80 to 120 r / min;

[0020] And / or, the etching treatment time is 1 to 1.5 hours.

[0021] In some embodiments, in step (4), the drying temperature is 80-120° C., and the mass content of free water in the washing material after drying is less than 500 ppm;

[0022] And / or, the particle size of the washing material after being pulverized by the jet mill is 3 to 20 μm.

[0023] In the second aspect, an embodiment of the present invention further proposes a porous silicon-carbon negative electrode material, and the porous silicon-carbon negative electrode material is prepared by the preparation method described in the first aspect.

[0024] The porous silicon-carbon negative electrode material in the embodiment of the present invention has high porosity and good cycle stability.

[0025] In a third aspect, an embodiment of the present invention further proposes the use of the porous silicon-carbon negative electrode material as described in the second aspect in a lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a SEM image of the porous silicon-carbon negative electrode material prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0027] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0028] Where values ​​are described herein as a range, it should be understood that such disclosure includes disclosure of all possible sub-ranges within that range, as well as specific values ​​falling within that range, regardless of whether a specific value or a specific sub-range is explicitly stated.

[0029] Herein, the words "comprises" and "includes" and variations thereof mean that other elements or integers which are permitted but not specifically described may be included.

[0030] In this article, the term "and / or" is merely a term used to describe the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone.

[0031] In a first aspect, an embodiment of the present invention provides a method for preparing a porous silicon-carbon negative electrode material, comprising the following steps:

[0032] (1) mixing nano-silicon and a binder emulsion, and then sequentially performing ultrasonic dispersion and freeze drying to obtain a nano-silica gel material;

[0033] (2) crushing the pine cone powder and the nano-silica gel material separately, mixing them, and then subjecting the mixture to high-temperature carbonization treatment to obtain a silicon-carbon composite material;

[0034] (3) stirring and mixing the silicon-carbon composite material with an acid solution, performing an etching treatment, filtering and washing the obtained etching solution to a pH value of 6 to 7, and obtaining a washed material;

[0035] (4) After the washed material is dried, it is subjected to air flow milling, sieving and demagnetization to obtain the porous silicon-carbon negative electrode material.

[0036] In some embodiments, in step (1), the mass ratio of the nano-silicon to the binder emulsion is (7-10):1, non-limiting examples include: 7:1, 8:1, 9:1, 10:1, etc.;

[0037] Preferably, the particle size of the nano-silicon is 20 to 60 nm, non-limiting examples include: 20 nm, 30 nm, 45 nm, 50 nm, 60 nm, etc.;

[0038] Preferably, the binder emulsion includes at least one of styrene-butadiene rubber emulsion, silane coupling agent A-171, silane coupling agent KH-560, and silane coupling agent KH-570.

[0039] By using a binder emulsion, it can provide better bonding force; and in the subsequent carbonization and drying process, the above-mentioned binder emulsion can stably aggregate, thereby ensuring the stability of the overall material; in addition, the selected binder emulsion has a large elastic modulus, which can make the pole piece rebound thickness low, and is used for the battery negative electrode to ensure the stability of the battery's internal structure.

[0040] In some embodiments, in step (1), the mixing time is 30 to 90 minutes, non-limiting examples include: 30 minutes, 45 minutes, 60 minutes, 75 minutes, 80 minutes, 90 minutes, etc.;

[0041] And / or, the ultrasonic dispersion time is 30 to 60 minutes, non-limiting examples are: 30 minutes, 45 minutes, 50 minutes, 60 minutes, etc.; the raw material particles can be prevented from agglomerating by ultrasonic dispersion treatment;

[0042] And / or, the freeze-drying time is 24 to 72 hours, non-limiting examples include: 24 hours, 30 hours, 36 hours, 40 hours, 48 ​​hours, 50 hours, 60 hours, 72 hours, etc.

[0043] In some embodiments, in step (2), the mass ratio of the pine cone powder to the nano-colloid material is (10-12):1, non-limiting examples include: 10:1, 10.5:1, 11:1, 11.2:1, 11.8:1, 12:1, etc. By using pine cone powder as a carbon source, the raw material source is wide, easy to obtain, and is a green resource; in addition, the derived carbon pores generated by pine cones after high-temperature carbonization are larger, and the reserved volume space is more, which can reserve more space for the expansion of silicon. And the inventors found through research that if the amount of pine cone powder added is too high, the capacity of the resulting material will be too low; but if the amount of pine cone powder added is too low, the cycle performance of the resulting material will be deteriorated. Therefore, it is advantageous to control the mass ratio of pine cone powder to nano-colloid material to (10-12):1 in the embodiment of the present invention.

[0044] Furthermore, the particle sizes of the crushed pine cone powder and the nano-colloid material are both 8 to 12 μm, non-limiting examples being: 8 μm, 10 μm, 12 μm, etc.

[0045] In some embodiments, in step (2), the process of high temperature carbonization treatment is: the mixture is first purified and impurized at 200°C for 30 to 60 minutes (non-limiting examples are: 30 minutes, 45 minutes, 50 minutes, 60 minutes, etc.) under an inert gas protection atmosphere, and then heated to 1200 to 1600°C (non-limiting examples are: 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, etc.) at a heating rate of 5 to 10°C / min (non-limiting examples are: 5°C / min, 8°C / min, 10°C / min, etc.), and kept warm for 1 to 3 hours (non-limiting examples are: 5 to 10°C / min). Restrictive examples include: 1h, 1.5h, 2h, 2.8h, 3h, etc.), and then cooled to room temperature; it should be noted that the porous silicon-carbon negative electrode material prepared in the embodiment of the present invention is mainly a carbon material. Therefore, if the carbonization temperature is too high, the graphite grain growth rate will be too fast and the specific surface area will be too large. If it is used for the negative electrode of the battery, it will increase the side reaction and greatly reduce the first effect; but if the carbonization temperature is too low, the carbon material structure transformation will be incomplete, there will be too many impurities and internal defects, and it will not work under high SOC state when used for the negative electrode of the battery. Therefore, it is advantageous for the embodiment of the present invention to control the carbonization temperature to 1200-1600°C;

[0046] Preferably, the inert gas includes at least one of nitrogen and argon, and the flow rate of the inert gas is 1-5 m / s, non-limiting examples include: 1 m / s, 3 m / s, 5 m / s, etc.

[0047] In some embodiments, in step (3), the acid solution includes at least one of hydrochloric acid solution, citric acid solution, sulfuric acid solution, and nitric acid solution;

[0048] Preferably, the mass concentration of the acid solution is 5-20%, non-limiting examples include: 5%, 8%, 10%, 12%, 15%, 20%, etc.

[0049] By adopting acid etching, the reaction speed is faster, and since the carbon source used in the embodiment of the present invention is pine cones, which are a kind of biomass, the fruit shells often contain lignin, which can react with acid to achieve the purpose of purification and internal pore formation. It can not only increase the surface area of ​​the silicon-carbon composite material, thereby providing more lithium ion embedding positions, but also enhance the interaction between silicon and carbon materials, which is beneficial to improving the electrochemical properties of the silicon-carbon composite material.

[0050] In some embodiments, in step (3), the stirring and mixing speed is 80 to 120 r / min, non-limiting examples include: 80 r / min, 100 r / min, 110 r / min, 120 r / min, etc.;

[0051] And / or, the etching treatment time is 1 to 1.5 hours, non-limiting examples include: 1 hour, 1.2 hours, 1.5 hours, etc.

[0052] In some embodiments, in step (4), the drying temperature is 80-120° C., non-limiting examples include 80° C., 100° C., 120° C., etc.; and the mass content of free water in the washing material after drying is less than 500 ppm;

[0053] And / or, the particle size of the washing material after being pulverized by the jet mill is 3 to 20 μm, non-limiting examples include: 3 μm, 5 μm, 10 μm, 15 μm, 18 μm, 20 μm, etc.

[0054] In the second aspect, an embodiment of the present invention further proposes a porous silicon-carbon negative electrode material, and the porous silicon-carbon negative electrode material is prepared by the preparation method described in the first aspect.

[0055] In a third aspect, an embodiment of the present invention further proposes the use of the porous silicon-carbon negative electrode material as described in the second aspect in a lithium-ion battery, which is used as a negative electrode active material in a lithium-ion battery.

[0056] The following are non-limiting examples and comparative examples of the present invention. It should be noted that the schemes of the comparative examples are not prior art and are only provided for comparison with the schemes of the embodiments and are not intended to limit the present invention. Unless otherwise specified, the various raw materials used in the embodiments and comparative examples are conventional commercial products or can be prepared by known methods.

[0057] Example 1

[0058] A method for preparing a porous silicon-carbon negative electrode material comprises the following steps:

[0059] (1) Nano-silicon with a particle size of 20 nm and styrene-butadiene rubber latex were mixed and stirred at a mass ratio of 7:1 for 60 minutes, and then ultrasonically dispersed for 30 minutes after stirring to prevent particle agglomeration. The mixed colloid liquid was then placed in a freeze dryer and freeze-dried for 24 hours to obtain a nano-silica gel material;

[0060] (2) Pine cone powder and nano-silica gel material were weighed in a mass ratio of 12:1, and then respectively placed in a jet mill for pulverization until the particle size of both was 10 μm (wherein the frequency of the screw feeder was set to 4 Hz, the frequency of the grading motor was set to 195 Hz, and the frequency of the pulverizing motor was set to 230 Hz); then the pulverized pine cone powder and nano-silica gel material were placed in a mixer for high-speed mixing, the stirring speed was controlled to be 400 rpm, and the mixing time was 30 min; then the mixture was placed in an atmosphere furnace, the mixture was first purified and impurized at 200 ° C for 30 min under a nitrogen atmosphere, and then heated to 1200 ° C at a heating rate of 8 ° C / min, and kept warm for 2 h (the flow rate of nitrogen was 2 m / s, and the volume concentration of oxygen in the atmosphere furnace was less than 50 ppm). After the high-temperature carbonization treatment was completed, it was cooled to room temperature to obtain a silicon-carbon composite material;

[0061] (3) The silicon-carbon composite material and a 5 wt % dilute hydrochloric acid solution were stirred and mixed at a stirring speed of 100 r / min for 1 h, and the etching treatment was performed. The obtained etching solution was filtered and then washed with clean water until the pH value of the washing water was 6 to 7, and then the washing was stopped to ensure that the residual dilute hydrochloric acid was completely removed to obtain a washing material;

[0062] (4) The washing material is placed in a blast drying oven and nitrogen is introduced to make the volume content of oxygen in the blast drying oven less than 10 ppm. The material is then dried at 80°C. The dried washing material is then subjected to air flow grinding to crush the washing material to a particle size of 12 μm. Finally, an electromagnetic demagnetizer is used for two-stage screening and demagnetization to make the ash content of the obtained material ≤0.05% and the magnetic material ≤0.5 ppm, thereby obtaining a porous silicon-carbon negative electrode material.

[0063] Example 2

[0064] A method for preparing a porous silicon-carbon negative electrode material comprises the following steps:

[0065] (1) Nano-silicon with a particle size of 30 nm and styrene-butadiene rubber latex were mixed and stirred at a mass ratio of 7:1 for 60 minutes, and then ultrasonically dispersed for 30 minutes after stirring to prevent particle agglomeration. The mixed colloid liquid was then placed in a freeze dryer and freeze-dried for 36 hours to obtain a nano-silica gel material;

[0066] (2) Pine cone powder and nano-silica gel material were weighed in a mass ratio of 11:1, and then respectively placed in a jet mill for pulverization until the particle size of both was 10 μm (wherein the frequency of the screw feeder was set to 4 Hz, the frequency of the grading motor was set to 195 Hz, and the frequency of the pulverizing motor was set to 230 Hz); then the pulverized pine cone powder and nano-silica gel material were placed in a mixer for high-speed mixing, the stirring speed was controlled to be 400 rpm, and the mixing time was 30 min; then the mixture was placed in an atmosphere furnace, the mixture was first purified and impurized at 200 ° C for 30 min under a nitrogen atmosphere, and then the temperature was increased to 1400 ° C at a heating rate of 8 ° C / min, and the temperature was kept for 2 h (the flow rate of nitrogen was 2 m / s, and the volume concentration of oxygen in the atmosphere furnace was less than 50 ppm). After the high-temperature carbonization treatment was completed, it was cooled to room temperature to obtain a silicon-carbon composite material;

[0067] (3) The silicon-carbon composite material and a 10 wt % dilute hydrochloric acid solution were stirred and mixed at a stirring speed of 100 r / min for 1.2 h, and the etching treatment was performed. The obtained etching solution was filtered and then washed with clean water until the pH value of the washing water was 6 to 7, and then the washing was stopped to ensure that the residual dilute hydrochloric acid was completely removed to obtain a washing material;

[0068] (4) The washing material is placed in a blast drying oven and nitrogen is introduced to make the volume content of oxygen in the blast drying oven less than 10 ppm. The material is then dried at 80°C. The dried washing material is then subjected to air flow grinding to crush the washing material to a particle size of 13 μm. Finally, an electromagnetic demagnetizer is used for two-stage screening and demagnetization to make the ash content of the obtained material ≤0.05% and the magnetic material ≤0.5 ppm, thereby obtaining a porous silicon-carbon negative electrode material.

[0069] Example 3

[0070] A method for preparing a porous silicon-carbon negative electrode material comprises the following steps:

[0071] (1) Nano-silicon with a particle size of 40 nm and styrene-butadiene rubber latex were mixed and stirred at a mass ratio of 7:1 for 60 minutes, and then ultrasonically dispersed for 30 minutes after stirring to prevent particle agglomeration. The mixed colloid liquid was then placed in a freeze dryer and freeze-dried for 48 hours to obtain a nano-silica gel material;

[0072] (2) Pine cone powder and nano-silica gel material are weighed in a mass ratio of 10:1, and then respectively placed in a jet mill for pulverization until the particle size of both is 10 μm (wherein the frequency of the screw feeder is set to 4 Hz, the frequency of the grading motor is set to 195 Hz, and the frequency of the pulverizing motor is set to 230 Hz); then the pulverized pine cone powder and nano-silica gel material are placed in a mixer for high-speed mixing, the stirring speed is controlled to be 400 rpm, and the mixing time is 30 min; then the mixture is placed in an atmosphere furnace, the mixture is first purified and impurized at 200 ° C for 30 min under a nitrogen atmosphere, and then the temperature is increased to 1600 ° C at a heating rate of 8 ° C / min, and the temperature is kept for 2 h (the flow rate of nitrogen is 2 m / s, and the volume concentration of oxygen in the atmosphere furnace is less than 50 ppm). After the high-temperature carbonization treatment is completed, it is cooled to room temperature to obtain a silicon-carbon composite material;

[0073] (3) The silicon-carbon composite material and a 20 wt % dilute hydrochloric acid solution were stirred and mixed at a stirring speed of 100 r / min for 1.3 h, and the etching treatment was performed. The obtained etching solution was filtered and then washed with clean water until the pH value of the washing water was 6 to 7, and then the washing was stopped to ensure that the residual dilute hydrochloric acid was completely removed to obtain a washing material;

[0074] (4) The washing material is placed in a blast drying oven and nitrogen is introduced to make the volume content of oxygen in the blast drying oven less than 10 ppm. The material is then dried at 80°C. The dried washing material is then subjected to air flow grinding to crush the washing material to a particle size of 14 μm. Finally, an electromagnetic demagnetizer is used for two-stage screening and demagnetization to make the ash content of the obtained material ≤0.05% and the magnetic material ≤0.5 ppm, thereby obtaining a porous silicon-carbon negative electrode material.

[0075] Figure 1 This is a SEM image of the porous silicon-carbon negative electrode material prepared in this embodiment. It can be seen from the image that the silicon-carbon negative electrode material has a porous structure with a high porosity, which provides a reserved space for silicon expansion.

[0076] Example 4

[0077] A method for preparing a porous silicon-carbon negative electrode material comprises the following steps:

[0078] (1) Nano-silicon with a particle size of 50 nm and styrene-butadiene rubber latex were mixed and stirred at a mass ratio of 7:1 for 60 min, and then ultrasonically dispersed for 30 min after stirring to prevent particle agglomeration. The mixed colloid liquid was then placed in a freeze dryer and freeze-dried for 48 h to obtain a nano-silica gel material;

[0079] (2) Pine cone powder and nano-silica gel material are weighed in a mass ratio of 10:1, and then respectively placed in a jet mill for pulverization until the particle size of both is 10 μm (wherein the frequency of the screw feeder is set to 4 Hz, the frequency of the grading motor is set to 195 Hz, and the frequency of the pulverizing motor is set to 230 Hz); then the pulverized pine cone powder and nano-silica gel material are placed in a mixer for high-speed mixing, the stirring speed is controlled to be 400 rpm, and the mixing time is 30 min; then the mixture is placed in an atmosphere furnace, the mixture is first purified and impurized at 200 ° C for 30 min under a nitrogen atmosphere, and then the temperature is increased to 1600 ° C at a heating rate of 8 ° C / min, and the temperature is kept for 2 h (the flow rate of nitrogen is 2 m / s, and the volume concentration of oxygen in the atmosphere furnace is less than 50 ppm). After the high-temperature carbonization treatment is completed, it is cooled to room temperature to obtain a silicon-carbon composite material;

[0080] (3) The silicon-carbon composite material and a 20 wt % dilute hydrochloric acid solution were stirred and mixed at a stirring speed of 100 r / min for 1.4 h for etching. The obtained etching solution was filtered and then washed with clean water until the pH value of the washing water reached 6 to 7, so as to ensure that the residual dilute hydrochloric acid was completely removed to obtain a washing material;

[0081] (4) The washing material is placed in a blast drying oven and nitrogen is introduced to make the volume content of oxygen in the blast drying oven less than 10 ppm. The material is then dried at 80°C. The dried washing material is then subjected to air flow grinding to crush the washing material to a particle size of 14 μm. Finally, an electromagnetic demagnetizer is used for two-stage screening and demagnetization to make the ash content of the obtained material ≤0.05% and the magnetic material ≤0.5 ppm, thereby obtaining a porous silicon-carbon negative electrode material.

[0082] Example 5

[0083] A method for preparing a porous silicon-carbon negative electrode material comprises the following steps:

[0084] (1) Nano-silicon with a particle size of 60 nm and styrene-butadiene rubber latex were mixed and stirred at a mass ratio of 7:1 for 60 min, and then ultrasonically dispersed for 30 min after stirring to prevent particle agglomeration. The mixed colloid liquid was then placed in a freeze dryer and freeze-dried for 48 h to obtain a nano-silica gel material;

[0085] (2) Pine cone powder and nano-silica gel material are weighed in a mass ratio of 10:1, and then respectively placed in a jet mill for pulverization until the particle size of both is 10 μm (wherein the frequency of the screw feeder is set to 4 Hz, the frequency of the grading motor is set to 195 Hz, and the frequency of the pulverizing motor is set to 230 Hz); then the pulverized pine cone powder and nano-silica gel material are placed in a mixer for high-speed mixing, the stirring speed is controlled to be 400 rpm, and the mixing time is 30 min; then the mixture is placed in an atmosphere furnace, the mixture is first purified and impurized at 200 ° C for 30 min under a nitrogen atmosphere, and then the temperature is increased to 1600 ° C at a heating rate of 8 ° C / min, and the temperature is kept for 2 h (the flow rate of nitrogen is 2 m / s, and the volume concentration of oxygen in the atmosphere furnace is less than 50 ppm). After the high-temperature carbonization treatment is completed, it is cooled to room temperature to obtain a silicon-carbon composite material;

[0086] (3) The silicon-carbon composite material and a 20 wt % dilute hydrochloric acid solution were stirred and mixed at a stirring speed of 100 r / min for 1.5 h, and the etching treatment was performed. The obtained etching solution was filtered and then washed with clean water until the pH value of the washing water was 6 to 7, and then the washing was stopped to ensure that the residual dilute hydrochloric acid was completely removed to obtain a washing material;

[0087] (4) The washing material is placed in a blast drying oven and nitrogen is introduced to make the volume content of oxygen in the blast drying oven less than 10 ppm. The material is then dried at 80°C. The dried washing material is then subjected to air flow grinding to crush the washing material to a particle size of 14 μm. Finally, an electromagnetic demagnetizer is used for two-stage screening and demagnetization to make the ash content of the obtained material ≤0.05% and the magnetic material ≤0.5 ppm, thereby obtaining a porous silicon-carbon negative electrode material.

[0088] Comparative Example 1

[0089] A method for preparing a silicon-carbon negative electrode material comprises the following steps:

[0090] (1) Nano-silicon with a particle size of 60 nm and styrene-butadiene rubber latex were mixed and stirred at a mass ratio of 7:1 for 60 min, and then ultrasonically dispersed for 30 min after stirring to prevent particle agglomeration. The mixed colloid liquid was then placed in a freeze dryer and freeze-dried for 48 h to obtain a nano-silica gel material;

[0091] (2) Pine cone powder and nano-silica gel material are weighed in a mass ratio of 10:1, and then respectively placed in a jet mill for pulverization until the particle size of both is 10 μm (wherein the frequency of the screw feeder is set to 4 Hz, the frequency of the grading motor is set to 195 Hz, and the frequency of the pulverizing motor is set to 230 Hz); then the pulverized pine cone powder and nano-silica gel material are placed in a mixer for high-speed mixing, the stirring speed is controlled to be 400 rpm, and the mixing time is 30 min; then the mixture is placed in an atmosphere furnace, the mixture is first purified and impurized at 200 ° C for 30 min under a nitrogen atmosphere, and then the temperature is increased to 1600 ° C at a heating rate of 8 ° C / min, and the temperature is kept for 2 h (the flow rate of nitrogen is 2 m / s, and the volume concentration of oxygen in the atmosphere furnace is less than 50 ppm). After the high-temperature carbonization treatment is completed, it is cooled to room temperature to obtain a silicon-carbon composite material;

[0092] (3) The silicon-carbon composite material is placed in a blast drying oven and nitrogen is introduced so that the volume content of oxygen in the blast drying oven is less than 10 ppm. The silicon-carbon composite material is then dried at 80°C. The silicon-carbon composite material is then subjected to air flow grinding until the particle size is 14 μm. Finally, an electromagnetic demagnetizer is used for two-stage screening and demagnetization so that the ash content in the obtained material is ≤0.05% and the magnetic matter is ≤0.5 ppm, thereby obtaining a silicon-carbon negative electrode material.

[0093] Comparative Example 2

[0094] A method for preparing a porous silicon-carbon negative electrode material comprises the following steps:

[0095] (1) Nano-silicon with a particle size of 15 μm and styrene-butadiene rubber latex were mixed and stirred at a mass ratio of 7:1 for 60 minutes, and then ultrasonically dispersed for 30 minutes after stirring to avoid particle agglomeration. The mixed colloid liquid was then placed in a freeze dryer and freeze-dried for 48 hours to obtain a nano-silica gel material;

[0096] (2) Pine cone powder and nano-silica gel material are weighed in a mass ratio of 10:1, and then respectively placed in a jet mill for pulverization until the particle size of both is 10 μm (wherein the frequency of the screw feeder is set to 4 Hz, the frequency of the grading motor is set to 195 Hz, and the frequency of the pulverizing motor is set to 230 Hz); then the pulverized pine cone powder and nano-silica gel material are placed in a mixer for high-speed mixing, the stirring speed is controlled to be 400 rpm, and the mixing time is 30 min; then the mixture is placed in an atmosphere furnace, the mixture is first purified and impurized at 200 ° C for 30 min under a nitrogen atmosphere, and then the temperature is increased to 1600 ° C at a heating rate of 8 ° C / min, and the temperature is kept for 2 h (the flow rate of nitrogen is 2 m / s, and the volume concentration of oxygen in the atmosphere furnace is less than 50 ppm). After the high-temperature carbonization treatment is completed, it is cooled to room temperature to obtain a silicon-carbon composite material;

[0097] (3) The silicon-carbon composite material and a 20 wt % dilute hydrochloric acid solution were stirred and mixed at a stirring speed of 100 r / min for 1.5 h, and the etching treatment was performed. The obtained etching solution was filtered and then washed with clean water until the pH value of the washing water was 6 to 7, and then the washing was stopped to ensure that the residual dilute hydrochloric acid was completely removed to obtain a washing material;

[0098] (4) The washing material is placed in a blast drying oven and nitrogen is introduced to make the volume content of oxygen in the blast drying oven less than 10 ppm. The material is then dried at 80°C. The dried washing material is then subjected to air flow grinding to crush the washing material to a particle size of 14 μm. Finally, an electromagnetic demagnetizer is used for two-stage screening and demagnetization to make the ash content of the obtained material ≤0.05% and the magnetic material ≤0.5 ppm, thereby obtaining a porous silicon-carbon negative electrode material.

[0099] Comparative Example 3

[0100] A method for preparing a porous silicon-carbon negative electrode material comprises the following steps:

[0101] (1) Nano-silicon with a particle size of 15 μm and styrene-butadiene rubber latex were mixed and stirred at a mass ratio of 7:1 for 60 minutes, and then ultrasonically dispersed for 30 minutes after stirring to avoid particle agglomeration. The mixed colloid liquid was then placed in a freeze dryer and freeze-dried for 48 hours to obtain a nano-silica gel material;

[0102] (2) Pine cone powder and nano-silica gel material are weighed in a mass ratio of 10:1, and then respectively placed in a jet mill for pulverization until the particle size of both is 10 μm (wherein the frequency of the screw feeder is set to 4 Hz, the frequency of the grading motor is set to 195 Hz, and the frequency of the pulverizing motor is set to 230 Hz); then the pulverized pine cone powder and nano-silica gel material are placed in a mixer for high-speed mixing, the stirring speed is controlled to be 400 rpm, and the mixing time is 30 min; then the mixture is placed in an atmosphere furnace, the mixture is first purified and impurized at 200 ° C for 30 min under a nitrogen atmosphere, and then the temperature is increased to 800 ° C at a heating rate of 8 ° C / min, and the temperature is kept for 2 h (the flow rate of nitrogen is 2 m / s, and the volume concentration of oxygen in the atmosphere furnace is less than 50 ppm). After the high-temperature carbonization treatment is completed, it is cooled to room temperature to obtain a silicon-carbon composite material;

[0103] (3) The silicon-carbon composite material and a 20 wt % dilute hydrochloric acid solution were stirred and mixed at a stirring speed of 100 r / min for 1.5 h, and the etching treatment was performed. The obtained etching solution was filtered and then washed with clean water until the pH value of the washing water was 6 to 7, and then the washing was stopped to ensure that the residual dilute hydrochloric acid was completely removed to obtain a washing material;

[0104] (4) The washing material is placed in a blast drying oven and nitrogen is introduced to make the volume content of oxygen in the blast drying oven less than 10 ppm. The material is then dried at 80°C. The dried washing material is then subjected to air flow grinding to crush the washing material to a particle size of 14 μm. Finally, an electromagnetic demagnetizer is used for two-stage screening and demagnetization to make the ash content of the obtained material ≤0.05% and the magnetic material ≤0.5 ppm, thereby obtaining a porous silicon-carbon negative electrode material.

[0105] The silicon-carbon negative electrode materials prepared in the above-mentioned embodiment and comparative example were respectively assembled into lithium-ion batteries and then subjected to charge-discharge cycle performance tests and porosity tests. The results are shown in Table 1.

[0106] Table 1

[0107] Porosity First capacity First efficiency Capacity retention after 400 weeks Example 1 51% 628mAh / g 81% 89% Example 2 53% 637mAh / g 83% 88% Example 3 54% 656mAh / g 84% 86% Example 4 56% 658mAh / g 86% 84% Example 5 58% 665mAh / g 89% 82% Comparative Example 1 23% 564mAh / g 71% 72% Comparative Example 2 43% 587mAh / g 71% 73% Comparative Example 3 55% 383mAh / g 65% 71%

[0108] As can be seen from Table 1, in Comparative Example 1, since acid etching is not used, the porosity of the obtained silicon-carbon negative electrode material is relatively low, and since lithium ions will directly react with silicon to form an alloy, resulting in expansion, the expansion process will cause the SEI film to increase, and more lithium ions are required to participate in the reaction, resulting in some lithium ions being unable to return to the positive electrode, which in turn leads to poor first efficiency and retention rate of capacity; in Comparative Example 2, due to the use of large-particle silicon powder, the expansion will be seriously aggravated, causing the structure of the negative electrode material to be pulverized, which will lead to a serious decrease in the first efficiency and retention rate; in Comparative Example 3, due to the use of large-particle silicon powder and the low carbonization temperature of only 800°C, there will be too many impurities such as volatile matter and sulfur in the silicon-carbon negative electrode material, which makes it difficult for lithium ions to enter the interior, resulting in too low material capacity, and there are a large number of metal salt substances inside, which are serious in self-discharge, so the first efficiency and capacity retention rate performance are also poor. In contrast, the porous silicon-carbon negative electrode material prepared in the embodiment of the present invention exhibits better electrochemical performance.

[0109] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0110] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a porous silicon-carbon negative electrode material, characterized in that: The following steps are involved: (1) mixing nano-silicon and a binder emulsion, and then sequentially performing ultrasonic dispersion and freeze drying to obtain a nano-silica gel material; (2) crushing the pine cone powder and the nano-silica gel material separately, mixing them, and then subjecting the mixture to high-temperature carbonization treatment to obtain a silicon-carbon composite material; (3) stirring and mixing the silicon-carbon composite material with an acid solution, performing an etching treatment, filtering and washing the obtained etching solution to a pH value of 6 to 7, and obtaining a washed material; (4) After the washed material is dried, it is subjected to air flow milling, sieving and demagnetization to obtain the porous silicon-carbon negative electrode material.

2. The method for preparing the porous silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (1), the mass ratio of the nano-silicon to the binder emulsion is (7-10):1; Preferably, the particle size of the nano-silicon is 20 to 60 nm; Preferably, the binder emulsion includes at least one of styrene-butadiene rubber emulsion, silane coupling agent A-171, silane coupling agent KH-560, and silane coupling agent KH-570.

3. The method for preparing the porous silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (1), the mixing and stirring time is 30 to 90 minutes, the ultrasonic dispersion time is 30 to 60 minutes, and the freeze-drying time is 24 to 72 hours.

4. The method for preparing the porous silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (2), the mass ratio of the pine cone powder to the nano-colloid material is (10-12):

1.

5. The method for preparing the porous silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (2), the process of the high-temperature carbonization treatment is as follows: the mixture is first purified and impurized at 200° C. for 30 to 60 minutes under an inert gas protection atmosphere, then heated to 1200 to 1600° C. at a heating rate of 5 to 10° C. / min, kept at this temperature for 1 to 3 hours, and then cooled to room temperature; Preferably, the inert gas includes at least one of nitrogen and argon, and the flow rate of the inert gas is 1 to 5 m / s.

6. The method for preparing the porous silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (3), the acid solution includes at least one of a hydrochloric acid solution, a citric acid solution, a sulfuric acid solution, and a nitric acid solution; Preferably, the mass concentration of the acid solution is 5-20%.

7. The method for preparing the porous silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (3), the stirring and mixing speed is 80 to 120 r / min; And / or, the etching treatment time is 1 to 1.5 hours.

8. The method for preparing the porous silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (4), the drying temperature is 80-120° C., and the mass content of free water in the washing material after drying is less than 500 ppm; And / or, the particle size of the washing material after being pulverized by the jet mill is 3 to 20 μm.

9. A porous silicon-carbon negative electrode material, characterized in that: The porous silicon-carbon negative electrode material is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the porous silicon-carbon negative electrode material as claimed in claim 9 in a lithium-ion battery.

Citation Information

Patent Citations

  • Biomass hard carbon negative electrode material for sodium ion battery, preparing method and sodium ion battery

    CN106299365A

  • Silicon-containing mineral-based porous silicon-carbon composite negative electrode material and preparation method thereof

    CN113871604A

  • Preparation method of porous silicon carbon negative electrode material

    CN116332154A

  • Dual mode supply circuit and method

    KR1020220113870A

  • Plant pompon hard carbon composite negative electrode material, and preparation method therefor and use thereof

    WO2023160017A1